2009
DOI: 10.1128/jb.01668-08
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Superdormant Spores of Bacillus Species

Abstract: Superdormant spores of Bacillus subtilis and Bacillus megaterium were isolated in 4 to 12% yields following germination with high nutrient levels that activated one or two germinant receptors. These superdormant spores did not germinate with the initial nutrients or those that stimulated other germinant receptors, and the superdormant spores' defect was not genetic. The superdormant spores did, however, germinate with Ca 2؉ -dipicolinic acid or dodecylamine. Although these superdormant spores did not germinate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
156
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(170 citation statements)
references
References 35 publications
9
156
5
Order By: Relevance
“…Previous studies have shown that carbonation with mild heating (<10 MPa, 20 _ 40℃) effectively inactivates vegetative bacterial cells and fungal cells (Watanabe et al, 2003). However, spores of various Bacillus species are metabolically dormant and are thus highly resistant to environmental stress factors (Ghosh and Setlow, 2009) including carbonation (Watanabe et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that carbonation with mild heating (<10 MPa, 20 _ 40℃) effectively inactivates vegetative bacterial cells and fungal cells (Watanabe et al, 2003). However, spores of various Bacillus species are metabolically dormant and are thus highly resistant to environmental stress factors (Ghosh and Setlow, 2009) including carbonation (Watanabe et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The t lag values were computationally obtained for more than 90% of spores imaged. The remaining spores were almost exclusively ones that did not germinate during the experiment, possibly because many of these spores were "superdormant" (6,7,34), and these spores were not analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…The two other B. subtilis strains used were PY79 derivatives and were PY79 (wild type) and PB705 (32) (prkC) (obtained from J. Dworkin). Spores of B. subtilis strains were prepared on 2ϫ SG agar plates without antibiotics at 37°C, and spores were incubated, harvested, and cleaned as described previously (6,19). The B. megaterium strain used was QM B1551 (ATCC 12872) (originally obtained from H. S. Levinson).…”
Section: Methodsmentioning
confidence: 99%
“…Although germination is an all-or-nothing process for each individual spore, subpopulations of spores appear to have different germination thresholds (Ghosh and Setlow, 2009a). This might reflect a stochastic process due to the low expression levels of Ger receptor proteins.…”
Section: Future Directionsmentioning
confidence: 99%
“…This might reflect a stochastic process due to the low expression levels of Ger receptor proteins. Indeed, spores that can only germinate when multiple Ger receptors are activated simultaneously have been isolated in B. subtilis, B. megaterium and B. cereus (Ghosh and Setlow, 2009a;Ghosh and Setlow, 2009b). Future work should elucidate whether differences in Ger receptors levels could account for these superdormant spores.…”
Section: Future Directionsmentioning
confidence: 99%